Regional cell-specific transcriptome mapping reveals regulatory complexity in the adult Drosophila midgut - Dutta, Devanjali; Dobson, Adam J.; Houtz, Philip L.; Gläßer, Christine; Revah, Jonathan; Korzelius, Jerome; Patel, Parthive H.; Edgar, Bruce; Buchon, Nicolas (Cell reports, 2015)
Deciphering contributions of specific cell types to organ function is experimentally challenging. The Drosophila midgut is a dynamic organ with five morphologically and functionally distinct regions (R1-R5), each composed of multipotent intestinal stem cells (ISCs), progenitor enteroblasts (EBs), enteroendocrine cells (EEs), enterocytes (ECs), and visceral muscle (VM). To characterize cellular specialization and regional function in this organ, we generated RNA-sequencing transcriptomes of all five cell types isolated by FACS from each of the five regions, R1-R5. In doing so, we identify transcriptional diversities among cell types and document regional differences within each cell type that define further specialization. We validate cell-specific and regional Gal4 drivers; demonstrate roles for transporter Smvt and transcription factors GATAe, Sna, and Ptx1 in global and regional ISC regulation, and study the transcriptional response of midgut cells upon infection. The resulting transcriptome database (http://flygutseq.buchonlab.com) will foster studies of regionalization, homeostasis, immunity, and cell-cell interactions.